Vertebral bone marrow fat, bone mineral density and diabetes: The Osteoporotic fractures in Men (MrOS) study - Sheu, Yahtyng (Bone, 2017)
Elevated vertebral bone marrow fat (BMF) among individuals with osteoporosis has been established in histomorphometric studies. Several studies have found a negative correlation between BMF and bone mineral density (BMD) at the spine in men and women across different age groups. Animal studies have also observed bone loss with increased BMF in mice with induced diabetes. Our study objective was to test the hypothesis that the association between BMF and BMD varies by diabetic status. We performed a cross-sectional study of 156 men aged 74–96 years from the Osteoporotic Fractures in Men study (MrOS) at the Pittsburgh clinical site. All men had spine BMF scans using proton magnetic resonance spectroscopy and spine and hip BMD scans by dual-energy x-ray absorptiometry. BMF was expressed as lipid to “lipid + water” ratio (%). Men were considered diabetic if they self-reported a physician diagnosis of diabetes, diabetes medication or had a fasting glucose ≥ 126mg/dl. Men with diabetes (n=38) had a significantly higher spine BMF (58.9 vs. 54.6 %, p=0.0035), spine BMD (1.20 vs. 1.10 g/cm(2), P=0.007)) and total hip BMD (0.99 vs. 0.94 g/cm(2), p=0.04) than those without, while no differences were observed for body weight, body mass index or waist circumference. Pearson correlation tests showed no significant correlation of spine BMF with age or BMD in non-diabetics. Significant inverse correlations were observed between BMF and BMD (−0.30 for femoral neck and −0.39 for total hip) among diabetic men. In conclusion, men with diabetes had a higher BMF compared to non-diabetic men. The correlation between BMF and BMD differed by diabetes status. Further investigation of the association of diabetes with BMF and BMD may provide a better understanding of the high fracture rates among individuals with diabetes despite their higher BMD.